Study on Curving Passing Performance of Rail Grinding Wagon Considering Car-Body Flexibility - Ziyang SONG; Maohai FU (机车电传动)
The passing speed is much lower than the design speed of curved track when rail grinding wagon performs the curve grinding operation, which results in the excess superelevation phenomenon. The rigid-flexible coupled dynamics model of rail grinding wagon was established using the FEM software ANSYS and the multi-body simulation software Simpack considering carbody flexibility. The contact relationship between the grinding wheels and rail was introduced in the model to study car-body elastic deformation on the dynamic performances. The dynamic responses of curve radius and superelevation were compared and analyzed under grinding operation conditions and free running. The results showed that the car-body elastic deformation mainly affected derailment coefficient and wheel unloading rate, but had little influence on the wheel axle lateral force and roll coefficient. After considering the car-body as a flexible body, curving passing performance of the rail grinding wagon had been improved. Within a certain range, increasing the curve radius and decreasing the superelevation could improve curving passing performance of vehicle. Grinding would worsen curving passing performance of vehicle and increase the risk of derailment.